Futsal match-related fatigue affects running performance and neuromuscular parameters but not finishing kick speed or accuracy - Milioni, Fabio [UNESP]; Vieira, Luiz H.P.; Barbieri, Ricardo A. [UNESP]; Zagatto, Alessandro M. [UNESP]; Nordsborg, Nikolai B.; Barbieri, Fabio A. [UNESP]; dos-Santos, Jï¿½lio W. [UNESP]; Santiago, Paulo R.P.; Papoti, Marcelo [UNESP] (Frontiers, 2016)
Purpose: The aim of the present study was to investigate the influence of futsal match-related fatigue on running performance, neuromuscular variables, and finishing kick speed and accuracy. Methods: Ten professional futsal players participated in the study (age: 22.2 ï¿½ 2.5 years) and initially performed an incremental protocol to determine maximum oxygen uptake (V.O2max: 50.6 ï¿½ 4.9 mL.kg-1.min-1). Next, simulated games were performed, in four periods of 10 min during which heart rate and blood lactate concentration were monitored. The entire games were video recorded for subsequent automatic tracking. Before and immediately after the simulated game, neuromuscular function was measured by maximal isometric force of knee extension, voluntary activation using twitch interpolation technique, and electromyographic activity. Before, at half time, and immediately after the simulated game, the athletes also performed a set of finishing kicks for ball speed and accuracy measurements. Results: Total distance covered (1st half: 1986.6 ï¿½ 74.4 m; 2nd half: 1856.0 ï¿½ 129.7 m, P = 0.00) and distance covered per minute (1st half: 103.2 ï¿½ 4.4 m.min-1; 2nd half: 96.4 ï¿½ 7.5 m.min-1, P = 0.00) demonstrated significant declines during the simulated game, as well as maximal isometric force of knee extension (Before: 840.2 ï¿½ 66.2 N; After: 751.6 ï¿½ 114.3 N, P = 0.04) and voluntary activation (Before: 85.9 ï¿½ 7.5%; After: 74.1 ï¿½ 12.3%, P = 0.04), however ball speed and accuracy during the finishing kicks were not significantly affected. Conclusion: Therefore, we conclude that despite the decline in running performance and neuromuscular variables presenting an important manifestation of central fatigue, this condition apparently does not affect the speed and accuracy of finishing kicks.
Keywords: Automatic tracking; EMG; Exercise physiology; Fatigue; Sport performance; Twitch Interpolation